Penerapan Pemberian Restitusi oleh Pelaku Bisnis Perdagangan Orang Kepada Korban Tindak Pidana Perdagangan Orang (TPPO) di Kota Batam - Alfi Ramadania (Journal of Law and Policy Transformation, 2021)
Material and immaterial restitution for victims of human trafficking as stipulated in Article 48 to Article 50 of Law Number 21 of 2007 concerning Eradication of Crime in Human Trafficking (UUPTPPO) so that efforts to fulfill these restitution are important to implement, which in this paper is specifically in the case of criminal law regarding human trafficking. The purpose of this study was to analyze the application of restitution by perpetrator of human trafficking to the victims of human trafficking (TPPOs), analyze and find juridical problems faced by law enforcement in imposing restitution on human trafficking and analyze solutions for restitution to victims of TPPO can be applied to human trafficking cases in Batam City. Data collection was carried out using primary and secondary data. The research method used in this writing is the Juridical Sociological method. The research results showed that the application of restitution by perpetrator of human trafficking to the victims of TPPO in the criminal justice system in Batam City was not in accordance with the laws and regulations, victims of TPPO had not received adequate legal protection, both material and immaterial protection, this condition was caused because law enforcement officials from the Police level never included the calculation of restitution in the minutes of the investigation (BAP) so that the Prosecutor's Office also did not include in the letter of indictment and the Court also did not decide on restitution in its ruling